2022
DOI: 10.1177/0958305x221094581
|View full text |Cite
|
Sign up to set email alerts
|

Clean energy, emission trading policy, and CO2 emissions: Evidence from China

Abstract: This paper constructs a unique dataset of clean energy and adopts static panel models and dynamic panel specifications to explore the correlation between clean energy and CO2 emissions. Furthermore, this paper employs the interaction term of pilot areas and pilot time as the proxy of emission trading policy to examine the effect of China’s emission trading pilot on clean energy. Then, this paper conducts quasi-natural experiments on CO2 emissions. Our findings show a negative correlation between CO2 emissions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…By using a quasi-natural experiment for 30 provinces in China from 2004 to 2019, Guo et al [18] confirmed the effectiveness of the carbon trading policy to lower regional carbon emissions. These results were also further confirmed by Yang and Wang [19]. In addition, Guo et al [20] argued that a carbon tax is an effective means of curbing carbon emissions and preventing global climate change, and this result was also echoed by Jia and Lin [21].…”
Section: Factors Influencing Carbon Emissionsmentioning
confidence: 62%
“…By using a quasi-natural experiment for 30 provinces in China from 2004 to 2019, Guo et al [18] confirmed the effectiveness of the carbon trading policy to lower regional carbon emissions. These results were also further confirmed by Yang and Wang [19]. In addition, Guo et al [20] argued that a carbon tax is an effective means of curbing carbon emissions and preventing global climate change, and this result was also echoed by Jia and Lin [21].…”
Section: Factors Influencing Carbon Emissionsmentioning
confidence: 62%
“…On the other hand, low and disordered standards for products have caused serious secondary pollution to the ecological environment. For example, an emission trading market pilot helps reduce carbon dioxide emissions (F. Yang & Wang, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, low and disordered standards for products have caused serious secondary pollution to the ecological environment. For example, an emission trading market pilot helps reduce carbon dioxide emissions (F. Yang & Wang, 2022). In September 2020, President Xi Jinping announced at the 75th session of the United Nations General Assembly that China will strive to realize peaking carbon emissions by 2030 and achieve carbon neutrality by 2060.…”
Section: Introductionmentioning
confidence: 99%